(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Consumer behavior is the study of how people, groups, and organizations choose, purchase,utilize, and discard products, services, concepts, or experiences to satiate their wants and desires.Because consumer behavior is malleable, it is never straightforward to understand it. They could reactto stimuli and make snap decisions because they are out of touch with their fundamental drives.Understanding why and how customers make purchases is beneficial for all marketers. You will makeserious advertising errors if you don’t comprehend the desires, wants, and preferences of your targetaudience. This research defines advertising, specifies its many forms, and makes recommendations forthe forms of advertising that are most appropriate for consumers and marketers.